2017
DOI: 10.1371/journal.pone.0181964
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of type 1 diabetes development and B-cell activation in nonobese diabetic mice by early life exposure to a diabetogenic environment

Abstract: Microbes, including viruses, influence type 1 diabetes (T1D) development, but many such influences remain undefined. Previous work on underlying immune mechanisms has focussed on cytokines and T cells. Here, we compared two nonobese diabetic (NOD) mouse colonies, NODlow and NODhigh, differing markedly in their cumulative T1D incidence (22% vs. 90% by 30 weeks in females). NODhigh mice harbored more complex intestinal microbiota, including several pathobionts; both colonies harbored segmented filamentous bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 77 publications
1
17
0
Order By: Relevance
“…Recent studies in Hashimoto's disease and other autoimmune conditions such as multiple sclerosis and type 1 diabetes are beginning to provide compelling links with gut microbiota in disease pathogenesis [41][42][43][44][45][46]. However, studies on Hashimoto's disease in the human and experimental mouse model provide contrasting results on the role of gut microbiota in disease development [41,47].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in Hashimoto's disease and other autoimmune conditions such as multiple sclerosis and type 1 diabetes are beginning to provide compelling links with gut microbiota in disease pathogenesis [41][42][43][44][45][46]. However, studies on Hashimoto's disease in the human and experimental mouse model provide contrasting results on the role of gut microbiota in disease development [41,47].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodent models of spontaneous type 1 diabetes (T1D) have linked the gut microbiota to disease susceptibility [62,63]. Studies in rodent models of spontaneous type 1 diabetes (T1D) have linked the gut microbiota to disease susceptibility [62,63].…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…Apart from allergy and asthma, the prenatal microbiome has also been implicated in other immune disorders, including type 1 diabetes and inflammatory bowel disease. Studies in rodent models of spontaneous type 1 diabetes (T1D) have linked the gut microbiota to disease susceptibility [62,63]. Livanos et al [64] demonstrated that administering a subtherapeutic lowdose penicillin (STAT) to mice during the late pregnancy period and postpartum accelerates the incidence of T1D in male offspring compared to untreated controls; however, whether these effects were mediated in the antepartum period is unclear.…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…Innate sensing can be altered by genetic variation, virus infections, and microbiome dysbiosis; all of which have been implicated in T1D ( 30 , 31 ). Certain differences in both the gut microbial communities and virome have recently been identified to be correlated with T1D development ( 32 , 33 ). For instance, butyrate- and acetate-producing bacteria have been associated with protection from spontaneous T1D in non-obese diabetic (NOD) mouse model of T1D ( 30 ).…”
Section: Therapeutic Use Of Butyrate To Alter Innate Epithelial Cell mentioning
confidence: 99%
“…Rather than simply removing cell subsets involved in T1D pathogenesis, the work of Dr. Piganelli exhibits how immune cell factors may be targeted and can potentially be programmed to adopt a more tolerogenic state. Recent literature has shown that environment early on in life is important for incidence of T1D in NOD mice and exposure to a “diabetogenic environment” is sufficient to promote incidence ( 32 ). It was also determined that composition of certain bacterial pathobionts can induce immunophenotypic changes in mice weaned in this “diabetogenic environment” and harbor B cells in gut-related lymphoid organs which are intrinsically more easily activated by local stimulation ( 32 ).…”
Section: Lag-3-mediated Immunoregulation Protects From T1dmentioning
confidence: 99%